The effects of the toughening mechanism and the molecular weights between cross-links on the fatigue resistance of epoxy polymer blends. (3rd May 2021) - Kishi, Hajime; Matsuda, Satoshi; Imade, Jin; Shimoda, Yusuke; Nakagawa, Takateru; Furukawa, Yoshio
Abstract: The fatigue resistance of epoxy polymer blends incorporating different types of preformed polymer particles was evaluated in terms of fatigue threshold and fatigue crack propagation (FCP). The fatigue thresholds of epoxies modified with polyamide-12 (PA12) particles were associated with higher stress intensity factor ranges ( ΔK ) than those of pure epoxies, irrespective of the molecular weights between cross-links ( Mc ). In contrast, the fatigue thresholds of epoxy blends with core-shell rubber (CSR) particles were affected by Mc . The FCP curve for a highly crosslinked CSR-toughened epoxy with Mc of 1110 g/mol was located at higher ΔK values compared with data for the corresponding pure epoxy. In contrast, the fatigue threshold of a moderately cross-linked CSR-modified epoxy with Mc of 2360 g/mol appeared in the lower ΔK range relative to the pure epoxy. Both cavitation of the CSR particles and plastic deformation of the latter epoxy were localized in a narrow area. Graphical abstract: Image 1 Highlights: Fatigue thresholds of epoxies with varying cross-link densities ( Mc ) were compared. Fatigue thresholds of epoxies with polyamide-12 particles increased regardless of Mc. Fatigue thresholds of epoxy blends with rubber particles depended highly on Mc.